Pemberdayaan Masyarakat Melalui Pesan Komunikasi Berbasis Sosial, Ekonomi dan Budaya untuk Pengembangan Wisata Pesisir di Kampung Bandar Pekanbaru - Zulkarnain Zulkarnain; Asnika Putri Simanjuntak; Lamun Bathara; Ardi Gustri Purbata; M. Irsyad Nur; Habib Irsya (Pelantar Press, 2025)
This study explores community empowerment through social, economic, and cultural communication in developing community-based tourism in Kampung Bandar, Pekanbaru. Using a qualitative approach supported by quantitative methods, the research aimed to provide a comprehensive understanding of community involvement in tourism management and promotion. Data was gathered from Focus Group Discussions (FGDs) with the Tourism Awareness Group and surveys from tourists visiting Kampung Bandar. The results indicate that community empowerment, which includes skill development, knowledge enhancement, and technology use, significantly influences tourism management and promotion. The community in Kampung Bandar acknowledges the importance of preserving local culture as a key tourism attraction, yet they still need further training in using digital technology, especially social media, for tourism promotion. Furthermore, strengthening communication networks among stakeholders such as local communities, tourism operators, and the government can speed up decision-making and foster collaboration in managing tourism destinations. Economic empowerment through micro-enterprises linked to tourism, such as local cuisine and handicrafts, has increased local income and boosted tourism competitiveness. This study suggests a need for capacity building, technology-focused training, and enhanced collaboration between the public and private sectors to maximize Kampung Bandar's tourism potential.